2010
DOI: 10.1007/s11111-010-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

Environment, transnational labor migration, and gender: case studies from southern Yucatán, Mexico and Vermont, USA

Abstract: Gender shapes the migration-environment association in both origin and destination communities. Using quantitative and qualitative data, we juxtapose these gender dimensions for a labor migrant-sending location of Mexico's southern Yucatán with those for a labor migrant-receiving location in Vermont (USA). We illustrate how in the southern Yucatán, circular transnational migration alters pasture, maize and chili production in a peasant field-forest system. Gender norms condition the land-use decisions of migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 56 publications
(52 reference statements)
1
40
0
Order By: Relevance
“…Third, the role of migration remittances is complex and may be either detrimental or beneficial with regard to environmental impacts in sending communities [89,90], which has seemed to motivate the growing number of case studies of livelihood diversification and environmental impacts in development. Gendered social relations and their role in agriculture and land use are an increasingly important focus of these studies [112,[172][173][174][175][176][177][178]. Yet research has not focused as systematically as we do here across the geographic and interdisciplinary integration of multiple forms of livelihood diversification (e.g., migration, on-farm diversification), environmental resource-and environment-specific systems (e.g., agrobiodiversity, soil, water, uncultivated biodiversity), and related gender relations.…”
Section: Results: Livelihood Diversification and Environmental Linkagesmentioning
confidence: 98%
See 1 more Smart Citation
“…Third, the role of migration remittances is complex and may be either detrimental or beneficial with regard to environmental impacts in sending communities [89,90], which has seemed to motivate the growing number of case studies of livelihood diversification and environmental impacts in development. Gendered social relations and their role in agriculture and land use are an increasingly important focus of these studies [112,[172][173][174][175][176][177][178]. Yet research has not focused as systematically as we do here across the geographic and interdisciplinary integration of multiple forms of livelihood diversification (e.g., migration, on-farm diversification), environmental resource-and environment-specific systems (e.g., agrobiodiversity, soil, water, uncultivated biodiversity), and related gender relations.…”
Section: Results: Livelihood Diversification and Environmental Linkagesmentioning
confidence: 98%
“…This research emphasis owes to the immediate impacts of soil and water management on human well-being as well as the potential reverse causation, namely, that soil or water degradation, or "agro-ecological drivers" more generally, contribute to the migration decisions of individuals and households [93,[176][177][178][179]. The importance of soil degradation in smallholder land use, for example, can be symptomatic of resource-poverty traps associated with livelihood diversification that is detrimental to both the environment and human well-being [61,173,174]. Water resources and management show a discernible trend toward increased quality (60%) under changes associated with on-farm livelihood diversification in contrast to migration, since the former often incorporates small-scale irrigation systems (Table 3.3b).…”
Section: Results: Livelihood Diversification and Environmental Linkagesmentioning
confidence: 99%
“…Oxkutzcab was the only place that was experiencing any in-migration, but none of it was related to agriculture. Out-migration was also linked to a reduction in area under cultivation in the Calakmul region (Busch & Geoghegan 2010, Radel, et al 2010, Schmook & Radel 2008. The 2000 census data showed that the service sector is the most important source of employment in Oxkutzcab whereas agriculture continued to provide the main source of livelihood for people in Peto and especially Tzucacab.…”
Section: Discussionmentioning
confidence: 99%
“…For example based on survey data from 1986-1997, Programa de Apoyos Directos al Campo (PRO-CAMPO), an agricultural program implemented in 1994 with the goal of integrating agricultural markets and intensifying production, revealed only modest increases in market production, but an increase in deforestation occurred through the conversion of land to commercial chili production and pastures (Klepeis & Vance 2003). A study based on household surveys carried out in 1997 and 2003 found that similar land use choices were being made by some, although others were choosing to withdraw from agriculture all together and those who converted their land to pasture or commercial agriculture were using less land than previously devoted to extensive agricultural practices, resulting in a decrease in deforestation (Busch & Geoghegan 2010, Radel et al 2010, Schmook & Radel 2008. The increase in global environmentalism over the last 25 years has also led to the development of community-based conservation programs in the region, such as the Parks in Peril program and Empleo Temporal, which along with the enforcement of rules associated with the reserve seem to be contributing to a decline in deforestation (Rueda 2010).…”
Section: Land Use/land Cover Change and Associated Drivers In The Yucmentioning
confidence: 99%
See 1 more Smart Citation